LoRa Sub Milliwatt Transceiver Design to Reduce Space Solutions Mass - Ali, Hessa (2022)
A Master of Science thesis in Electrical Engineering by Hessa Ali Hussain Ahmed Ali entitled, “LoRa Sub Milliwatt Transceiver Design to Reduce Space Solutions Mass”, submitted in May 2022. Thesis advisor is Dr. Lutfi Albasha. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).